Pelaksanaan Proses Asuhan Gizi Terstandar Pemberian Diet Diabetes Melitus, Rendah Purin, dan Rendah Lemak terhadap Pasien Diabetes Melitus Tipe 2 dan Suspect Cerebrovascular Accident: Sebuah Laporan Kasus - Santosa, Faradyah Lulut (Media Gizi Kesmas, 2024)
Background: Patients with type two diabetes mellitus and suspected cerebrovascular accident accompanied by hemiparesis require proper nutritional care to speed up the healing process. The nutritional care provided is a diabetes mellitus diet, low in purines and low in fat in order to keep blood glucose levels close to normal by maintaining a balanced diet and regulating food intake, as well as reducing fat levels to near normal by controlling cholesterol intake. Objectives Analyzing the Standardized Nutrition Care Process carried out on type two diabetes melitus and susp cerebrovascular accident patients hospitalized at X hospital. Methods: This clinical nutrition care rotation study used a descriptive research type with a case study design. The case study was conducted in September 2022 for inpatients at X Hospital in Surabaya. Results: Patients were given a cardiovascular diabetes mellitus diet with low purines and low fat and an energy requirement of 1755 kcal, 65.81 g of protein, 307.125 g of carbohydrates, and 29.25 g of fat. soft food form. After three days of monitoring, the results of the presentation of the portion of the meal increased in the food that had been served: the patient ate more than 75% of the food (remaining 25%). Patients do not eat food from outside the hospital. Conclusions: Some nutrients from the patient's food intake have reached 90–110% of the requirement. This is because the patient has no problems eating and, before hospital admission, already had a good appetite. The advice given is that it is better to be able to maintain restrictions on intake of sugar, salt, and fat and apply the 3J pattern, namely the right type, right amount, and right schedule. Apart from that, do light exercise to train muscles and body movements, such as stretching your hands as well as during discharge from the hospital, you can continue to change your diet according to recommendations (foods to avoid or limit) during hospitalization.